THE RELATIONSHIP BETWEEN THE PRESENCE OF AEDES SPP. LARVAE WITH CASES OF DENGUE HERMORRHAGIC FEVER - Andyra Priandhana; Gita Dwi Prasasty; Dwi Handayani; Dalilah Dalilah (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Dengue hemorrhagic fever is an infectious disease caused by dengue virus and transmitted through the Aedes spp. Prevention of dengue hemorrhagic fever can be done by eradicating the presence of Aedes spp. larvae in their breeding sites. This study aimed to determine whether there was a relationship between the presence of Aedes spp. mosquito larvae with the incidence of dengue hemorrhagic fever in the working area of Puskesmas Padang Selasa Kecamatan Ilir Barat I Palembang in 2019. This study was an analytic observational study with cross-sectional design. The research sample consisted of 110 houses, along with water reservoirs and mosquito larvae in it, which were chosen with purposive and simple random sampling technique. Research respondents were residents of the house chosen as the sample. Data collected by interview, observation, and microscopic identification. Data was processed and analyzed with the chi-square statistical test. Out of 110 houses visited, 26 (23.6%) of the respondents stated that they themselves or their household relatives had experienced DHF in the last two years. Out of the 332 water reservoirs observed, 36 (32.7%) were positive for Aedes spp. larvae, 14 (53.8%) of them were found in houses where residents had a history of DHF in the last 2 years. Chi-square statistical test results with a degree of confidence of 95% and ? 0.05 showed a significant relationship between the two variables with a p value = 0.017 and PR (prevalence rate) 2.339 (95% CI = 1.239-4.61). There was a significant relationship between the presence of Aedes spp. mosquito larvae with the incidence of dengue hemorrhagic fever in the working area of the Puskesmas Padang Selasa Kecamatan Ilir Barat I Palembang in 2019.